The taxonomic status of Aphis rostellum (Zhang, Chen, Zhong & Li, 1999) and description of the fundatrix and sexual morphs of Aphis umbrella (Börner, 1950) (Hemiptera: Aphidoidea) - Stekolshchikov, Andrey V.; Buga, Sergey V. (Zootaxa, 2017)
Aphis rostellum (Zhang, Chen, Zhong & Li, 1999) is placed as a new subjective synonym of A. umbrella (Börner, 1950). Detailed descriptions are provided of the fundatrix, oviparous female and male of this species.